Disparitas Estimasi Prevalensi Status Gizi Balita Berdasarkan Data e-PPGBM Dan SSGI di Kabupaten Aceh Selatan Tahun 2022-2024 - Dwi Anggia; Teungku Nih Farisni; Rubi Rimonda; Onetusfifsi Putra; Wintah Wintah (Universitas Pahlawan Tuanku Tambusai, 2026)
Nutritional status of children under five is an important indicator of public health quality, which in Indonesia is monitored through two systems: the Indonesian Nutritional Status Survey (Survei Status Gizi Indonesia/SSGI), a probability-based survey, and the Community-Based Nutrition Recording and Reporting electronic system (e-PPGBM), a routine recording system, which often produce differing prevalence estimates. This study aims to describe the magnitude of disparity in prevalence estimates of under-five nutritional status (stunting, wasting, underweight) between SSGI and e-PPGBM data in Aceh Selatan District during 2022–2024, as well as to examine possible underlying methodological factors. This study employed a descriptive-comparative design based on secondary data, analyzing all available annual aggregate SSGI and e-PPGBM data for Aceh Selatan District during 2022–2024, which were analyzed descriptively and quantitatively using Absolute Difference (AD), Disparity Ratio (DR), and Relative Difference (RD) measures. The results showed that all nutritional status indicators exhibited consistent disparities throughout the observation period, with the highest DR found for stunting (mean 8.00 times; AD 31.42 percentage points; RD 86.19%), followed by underweight (DR 4.11 times) and wasting (DR 3.45 times), and the trend directions of SSGI and e-PPGBM frequently diverged. Although this study did not directly analyze the causes of the disparity, the differences can be attributed to the methodological characteristics of the two systems as described in various literature. Both data sources need to be utilized complementarily to support decision-making and evaluation of nutrition programs.